Treatment for preschool age children who stutter : Protocol of a randomised, non-inferiority parallel group pragmatic trial with Mini-KIDS, social cognitive behaviour treatment and the Lidcombe Program-TreatPaCS - Leclercq, Anne-Lise; Waelkens, Veerle; Roelant, Ella; Allegaert, Mathias; Verhaegen, Iris; Claes, Kim; Dauvister, Estelle; Snijders, Steffi; Eggers, Kurt; Moyse, Astrid; Van Eerdenbrugh, Sabine (Public Library of Science (PLoS, 2025)
Stuttering is a speech disorder in which the flow of speech is disrupted by involuntary repetitions of sounds, syllables, words or phrases, stretched sounds or silent pauses in which the person is unable to produce sounds and sound transitions. Treatment success is the highest if stuttering is treated before the age of 6 years, before it develops into "persistent" stuttering. Stuttering treatment programs that focus directly on the speech of the child, like the Lidcombe Program, have shown to be effective in this age group. Mini-KIDS is also a treatment that focuses directly on the speech of the child. It is possible that capturing the increased brain plasticity at this age in combination with creating optimal conditions for recovery underlie these treatments' success rate. A treatment focusing on the cognitions, emotions and behaviour of the child, the social cognitive behaviour treatment (SCBT), is also frequently delivered in Belgium. In this study we want to compare, and collect data on the effectiveness, of these three treatment programs: Mini-KIDS, SCBT and the Lidcombe Program (protocol registered under number NCT05185726). 249 children will be allocated to one of three treatment groups. Stuttering specialists will treat the child (and guide the parents) with Mini-KIDS, the SCBT or the Lidcombe Program. They will be trained to deliver the programs meticulously. At 18 months after randomisation, the speech fluency of the child and the attitude of the child and parent(s) towards speech will be measured. It is expected that the three programs will achieve the same (near) zero levels of stuttering in nearly all children and a positive attitude towards speech at 18 months after the start of treatment. The amount of treatment hours to reach the (near) zero levels of stuttering will be compared between the different programmes. For families as well as for the health system this could generate important information.